Peran Logika dalam Prespektif Iman Kristen: Tantangan dan Manfaat - Ebenezer Gulo; Denisman Laia; Mozes Lawalata (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
In this article, we illustrate the importance of combining logic and Christian faith in everyday life, as well as the challenges and benefits associated with this. This article emphasizes that logic is a powerful tool in strengthening religious beliefs. By using logic, one can critically consider religious teachings and seek a deeper understanding of one's beliefs. This is one of the things that helps a person feel more confident in his faith because he understands the reasons behind that belief. This article shows the challenges faced when combining logic and Christian faith. Sometimes religious beliefs seem to conflict with logic or rationality and can cause internal conflict within a person. The method used is library research based on qualitative methods. This research aims to contribute thinking about the role of logic in the perspective of Christian faith, by reviewing its benefits and challenges.